2015
DOI: 10.1088/1748-3190/10/1/016014
|View full text |Cite
|
Sign up to set email alerts
|

To err is robotic, to tolerate immunological: fault detection in multirobot systems

Abstract: Abstract. Fault detection and fault tolerance represent two of the most important and largely unsolved issues in the field of multirobot systems. Efficient, long-term operation requires an accurate, timely detection, and accommodation of abnormally behaving robots. Most existing approaches to fault-tolerance prescribe a characterisation of normal robot behaviours, and train a model to recognise these behaviours. Behaviours unrecognised by the model are consequently labelled abnormal or faulty. Multirobot syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 40 publications
0
41
0
Order By: Relevance
“…Although our experiments confirmed that swarm behaviors inherently have some degree of tolerance for individual faults, in real-world applications it may be necessary to guarantee that faulty individuals will not compromise the whole swarm. Approaches for fault detection [80], fault tolerance [81], and online adaptation [79] must therefore be implemented in the system.…”
Section: Prominent Challenges Includementioning
confidence: 99%
“…Although our experiments confirmed that swarm behaviors inherently have some degree of tolerance for individual faults, in real-world applications it may be necessary to guarantee that faulty individuals will not compromise the whole swarm. Approaches for fault detection [80], fault tolerance [81], and online adaptation [79] must therefore be implemented in the system.…”
Section: Prominent Challenges Includementioning
confidence: 99%
“…There has been previous mention of work by several researchers toward fault detection in swarm robotics systems [12], [7], [10], [16]. In each piece of work, the fundamental mechanism that enables a fault to be detected can be essentially reduced to the comparison of an individual's observed behaviour to that which the swarm or observer expects it to exhibit.…”
Section: Behaviour Characterisationmentioning
confidence: 99%
“…Following this process leads to the following BFV that is proposed to be sufficiently representative of the aforementioned behaviours. Following Tarapore et al [16], the BFV described here is a concatenation of five individual binary features, where a returned value of 1 or 0 indicates the presence or absence of the feature, respectively:…”
Section: Deriving Behavioural Features From Robot Behavioursmentioning
confidence: 99%
See 2 more Smart Citations